Job recruiting system using sorting Algorithm / Adi Asyraf Ayob - Ayob, Adi Asyraf (2020)
In current modern era where the number of people who seeking job keep increasing, companies and organizations are having difficulty in choosing new workers. As for IT company that need high-quality employees to be hire into the firm, it is a challenging process since there is a lot of candidates who are having expertise in various kind of skills and knowledge. This is because the process consume time for the company human resources department to manually review and analyses every candidates who apply for the job. The purpose of this project is to develop a web-based job recruiting system with implementation of sorting algorithm. The sorting algorithm will assist the recruiters in selecting best job candidate by assigning score to each applicants and sort the applicant list by the finest score value. The requirements of the system was first identified by interview session with an IT company before proceeding to system design and development which involve process of designing prototype and scripting the system coding. The functionality of the prototype was tested using Test Script while the usability testing was performed by collecting response from the system users about the usefulness, ease of use, and satisfaction. The Job Recruiting System provide the solution for IT companies and organizations to choose best amongst the best workers into the firm.